Early intervention program by ICF model for babies of 4-18 months frequenting daycare center: protocol for clinical trial - Tainá Ribas Mélo; Luize Bueno de Araujo; Bruna Yamaguchi; Manoela de Paula Ferreira; Vera Lúcia Israel (Universidade Estadual Paulista (UNESP), 2019)
Abstract Introduction: A daycare center is a long-term place for infants, which means that early intervention programs should be thought of in this environment. There are still many gaps regarding the best way of stimulation/intervention, duration and description of effects and controlled outcomes. Aim: The objective of this clinical trial is to propose an early physical activity intervention program performed in infants of 4-18 months with risk/delay and with typical development at infant's daycare. Method: The protocol of this study is indicated for a controlled trial, in a crossover format, to be applied in 4 groups composed by in 4-18 month-old infants who attend daycare: Intervention group 1 Typical, Intervention group 1 Risk/delay, group Intervention 2 Typical, group Intervention 2 Risk/delay, in 4-18 month old infants who attend daycare. The ICF criteria about functions and structure (through evaluation questionnaire) are considered, as well as activities and participation (AIMS, Denver II, and PedsQl™ evaluation), personal characteristics (questionnaire, ABEP and AHEMD-IS) and environmental factors (AHEMD-IS). Conclusion: This original proposal can highlight a low-cost intervention program performed in a daycare environment verifying the infant's NMD in a systematized way using theoretical basis.